Dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) in patients with chronic coronary artery disease (CAD) - current state of knowledge and perspective for further research - Hubert Bochenek; Anna Bielicka; Michał Bzoma; Julia Gugulska; Irmina Czerepak; Marcin Kapij; Karolina Niewczas; Adrianna Brzozowska (Journal of Education, Health and Sport)
Introduction and purpose: aa Chronic coronary artery disease (CAD) is a prevalent condition affecting millions of people worldwide, significantly reducing quality of life and increasing the risk of myocardial infarction (MI). Percutaneous coronary intervention (PCI), often combined with stent implantation, is a cornerstone of CAD treatment. However, it induces a prothrombotic state, necessitating dual antiplatelet therapy (DAPT) to mitigate the risk of thrombosis and MI. Despite its established role, the optimal duration and specific composition of DAPT still remain under investigation. This article aims to summarise current knowledge on DAPT and highlight gaps requiring further research.